Operational performance measurement model based on knowledge management to reduce orders returned for a distribution company - Burga, Mario (2019)
Small and medium-sized enterprises (SMEs) in Peru present problems such as access to the national market due to limited capital or access to technology compared to large companies. However, they also lack an adequate definition and conceptualization of their processes, as well as a low level of business information transfer, which causes an absence in the measurement, control of processes and low operational performance. Given this situation, we propose the application and implementation of knowledge management tools in a company dedicated to the marketing and distribution of school supplies, which represents an SME in Peru. The tools used as the map of processes and flowcharts of the different processes were used to make the participants of the processes known. Through the realization of training, performance evaluations and internal audit, the learning of the operator is analyzed. As a result, there was a 57.63% decrease in errors in armed orders during picking, as well as a decrease of 7.98% and 8.59% of times in the execution of the processes under study for small orders and larger orders, respectively. Similarly, 96.56% of dispatches generated correctly were obtained.